Prevention of Motile Aeromonas Septicemia Disease with (Muntingia calabura L) to Striped Catfish (Pangasianodon hypophthalmus) - Hafil Kurnia Tama; Iesje Lukistyowati; Henni Syawal (Jurnal Akuakultur SEBATIN, 2024)
This research was held from December 2020 – February 2021 at the Laboratory of Fish Parasites and Diseases, Faculty of Fisheries and Marine Science, Universitas Riau. The purpose of this study was to analyze and obtain the best dose of cherry leaf solution to prevent Motile Aeromonas Septicemia from total erythrocytes, hematocrit and hemoglobin levels of striped catfish (Pangasianodon hypophthalmus) fish. The method used to experiment with Completely Randomized Design (CRD) is one factor of five treatment levels. The doses used were negative control without soaking the cherry leaf solution and not tested against Aeromonas hydrophila, positive control without soaking the cherry leaf solution and tested against A. hydrophila, soaking the cherry leaf solution with a dose of 2800 ppm (P1), 3,200 ppm (P2), and 3,600 ppm (P3). Immersion was performed five times for 5 minutes with an interval of 7 days. The results showed that soaking with cherry leaf solution at a dose of 3,600 ppm (P3) was the best dose (P<0.05) with a total value of erythrocytes after the challenge test of 209,66 x 104 cells/mm3, hematocrit level of 37%, hemoglobin 11.86 g/dL, and the survival rate of the test fish was 86,67%.